Masculinities under Neoliberalism - Abril Morales, Paco (Quaderns de l’Institut Català d’Antropologia, 2019)
Cornwall, Andrea; Karioris, Frank G.; Lindisfarne, Nancy, Ed. (2015) Masculinities Under Neoliberalism London: Zed Books, 285 p. ISBN: 978-1-78360-766-2